MANDIBULAR DEVIATION IN UNILATERAL CHEWING HABITS - Hidajah, Norman; Virtika Ayu, Ketut; Syahrul, Dwis (Faculty of Dentistry, Mahasaraswati Denpasar University, 2021)
Introduction: The mandibular movement pattern was used to evaluate the presence of a dysfunction. Impaired TMJ function is called temporomandibular disorder (TMD). One of the causes that are often associated with TMD is a bad habit of chewing one side. This habit is often done without realizing it, causing an imbalance in the distribution of the chewing load and can result in deviation or displacement. The occurrence of TMD can be characterized by limited mouth opening of less than 40 mm. Objective: This study aims to determine the presence of abnormalities in the pattern of mandibular movement in the bad habit of chewing on one side. Methods: The research method used is descriptive observational research with saturated sampling technique with a sample of 25 students of the Faculty of Dentistry, Mahasaraswati University Denpasar, class of 2017. Data collection was carried out by observing through videos of mandibular movement patterns. Results and conclusions: The results showed the pattern of mandibular movement with the habit of chewing on one side, in men who deviated 28%, in women 32%, while in men who did not deviate 12% and in women as much as 28%.